2012
DOI: 10.4329/wjr.v4.i7.318
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent use of aromatase inhibitors and hypofractionated radiation therapy

Abstract: AIM:To retrospectively assess the acute and long-term toxicity using aromatase inhibitors (AI) therapy concurrently with hypofractionated radiotherapy (HFRT) in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Concurrent AI did not decrease the efficacy of irradiation at a median follow-up of 26 months. Moreover, Chargari et al [ 15 ] (2012) evaluated the toxicity of concurrent use of AI and hypofractionated RT in 19 patients. At the end of the RT course, acute toxicity was low in most patients, with only 1 grade 3 cutaneous toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Concurrent AI did not decrease the efficacy of irradiation at a median follow-up of 26 months. Moreover, Chargari et al [ 15 ] (2012) evaluated the toxicity of concurrent use of AI and hypofractionated RT in 19 patients. At the end of the RT course, acute toxicity was low in most patients, with only 1 grade 3 cutaneous toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Several cases of pneumopathy with anti-aromatase have been reported [35,38,39] and the time to start adjuvant hormonotherapy in patients who will receive postoperative radiotherapy remain controversial moreover with hypofractionnated scheme in which dose per fraction can rise 2.67 to 6 Gy [40,41]. A study shown mild to moderate toxicity but not designed for assessment of lung toxicity [42]. Treatment should depend on the severity of clinical conditions, and considering the adverse effects of prolonged corticosteroids and risk of relapse [43].…”
Section: Discussionmentioning
confidence: 99%
“…We would like also to mark in the conclusion that clinical tests have been successfully conducted lately with application of hyperfractionation in those cases when usually traditional prolonged courses of tumor irradiation had been used [12,13], including the cases when the tumor irradiation scheme was applied-once a week [14,15], and in palliative ray therapy [16,17].…”
Section: Discussionmentioning
confidence: 99%